Myths, martyrs, and modernity : studies in the history of religions in honour of Jan N. Bremmer - Bremmer, Jan N.; Dijkstra, Jitse H. F.; Kroesen, J. E. A. 1975-; Kuiper, Y. (Numen Book Series, 2010)
This volume in honour of Jan N. Bremmer contains the contributions of numerous students, colleagues, and friends offered to him on the occasion of his 65th birthday. Throughout his career, Bremmer has distinguished himself as an internationally renowned scholar of religion both past and present, including first and foremost Greek and Roman religion, but also early Christianity and post-classical developments in religion and spirituality. In line with these three main areas of Bremmer's research, the volume is divided into three parts, bringing together contributions from distinguished scholars in many fields. The result is a diverse book which provides a broad spectrum of original ideas and innovative approaches in the history of religions, thus reflecting the nature of the scholarship of Bremmer himself.